PENGUATAN KEDUDUKAN DAN KEWENANGAN KONSTITUSIONAL DPD RI DALAM PERSPEKTIF UUD NEGARA RI TAHUN 1945 - Damrah Mamang (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2020)
The dynamics in the system and structure of the Indonesian constitution began in the reform era so quickly developed. All can run properly and correctly because it was initiated by reforming the constitution through an amendment or constitutional amendment mechanism (the 1945 Constitution) in four stages of change (1999 - 2002). One of the essence of the amendment, gave birth to the Regional Representative Council (DPD RI) as a state institution with its constitutionality can be found explicitly in Chapter VIIA Article 22 C Paragraph 1 - Paragraph 4 and Article 22 D Paragraph 1 - Paragraph 4. And UUNO. 17 of 2014 Jo UUNo.2 of 2018 concerning the MPR, DPR, DPD, DPRD. As a new post-amendment state institution, the DPD is designed as a strong bicameral second chamber of our parliament which was originally only unicameral, namely the DPR RI as a state institution and a representative institution of the people. But one of the characteristics of bicameral is if both parliamentary chambers carry out the legislative function as they should. However, if examined carefully until now based on the substitution of article 22 C and Article 22D of the 1945 Constitution of the Republic of Indonesia in 1945 the authority and authority of the DPD is still very limited. So that as an organic law does not give much space for the implementation of authority to the DPD in carrying out its main duties and functions, especially the legislative function like the DPR. For this reason, in order to strengthen and empower the future, the DPD's consistency and authority need to get priority place in the context of the subsequent amendments to the 1945 Constitution of the Republic of Indonesia as the Holder of strategic and fundamental national political decision authority. Everything is inseparable from the problems in the DPD now is a matter of the authority granted by the constitution to him, especially in the context of the legislative function to make laws. Its existence is expected to bridge the relationship between the center and the regions, in a two-chamber parliamentary frame which has strong bicameralism authority.